Biocontrol effects of Bacillus velezensis and Bacillus subtilis against strawberry root rot caused by Neopestalotiopsis clavispora - Ning, Jin; Ning, Tiao; Jin, Lu; Li, Qiongfen; Niu, Yanfen; Chen, Zebin; Han, Chengchou; Tang, Yilian; Deng, Changjun; Xie, Yingying; Zhao, Mingfang; Cui, Xingguo; et al. (Frontiers in Microbiology, 2025)
Strawberry root rot, caused by Neopestalotiopsis clavispora, is an emerging disease that seriously threatens the sustainable development of the strawberry industry. To develop eco-friendly control strategies, three antagonistic bacterial strains were screened from healthy strawberry plants and rhizosphere soils. Based on morphological characteristics, physiological and biochemical identification, and 16S rDNA sequence analysis, the isolates QY-4 and QJ-3 were identified as Bacillus velezensis, while TT-3 was identified as Bacillus subtilis. The results indicated that the cell-free culture filtrates of QY-4, QJ-3, and TT-3 significantly inhibited the hyphal growth of N. clavispora by disrupting cell membrane integrity, with inhibition rates of 63.29, 69.4, and 73.57%, respectively. Volatile organic compounds produced by these strains, evaluated using the plate pair method, effectively inhibited hyphal growth through aerial diffusion with inhibition rates of 47.76, 44.99, and 32.44%. Broad-spectrum antagonistic activity against several phytopathogenic fungi, including Colletotrichum acutatum, Alternaria alternata, and Botrytis cinerea, was observed with inhibition rates ranging from 50.37 to 78.88%. Through the antibiotic marker method, the labeled strains were shown to translocate from roots to stems and leaves following root irrigation treatment, establishing stable colonization in both strawberry tissues and rhizosphere soils. The application of these antagonistic strains significantly alleviated root rot symptoms and markedly reduced the disease index, with values of 36.98, 42.19, and 27.92, corresponding to disease control efficiencies of 56.28, 50.12, and 67%, respectively. Additionally, significant enhancement of superoxide dismutase, peroxidase, and catalase was observed in leaves, indicating the induction of host resistance. These findings demonstrate the dual role of QY-4, QJ-3, and TT-3 as biocontrol agents, by combining antifungal activities with resistance induction, thus offering promising candidates for the sustainable management of strawberry root rot.